Digitalização de deformações físicas do solo por meio de uma câmera digital - Coelho, Diego Eduardo Costa (2016)
Soil is a natural body composed by parcels in solid, liquid and gaseous state that contains living matter and occupy the greater portion of the earth surface. The agriculture development is based among thers in mechanization that has been important to get higher productivities. However, the intense use of machinery and implements in agriculture requires knowledge of their interaction with the soil, in order to reduce the damages that bring problems to the development of the cultures and to the environment. In this context, it is necessary to understand the effects of the tractor is tires during the transit on agricultural areas. Thus, this study aimed to evaluate the deformation of soil when trafficked by agricultural machinery through the Moiré technique and to propose a methodology for scanning the soil profile in comparison to the traditional methods. The work was divided in two stages: In the laboratory environment and in the field. In the first stage, we have scanned a styrofoam hemisphere, in order to find the best equipment available, as an essential preparation for the next stage. In the second step as repeated five plots, in order to evaluate the soil profile behavior and observed by means of two traditional techniques and also by the optical technique of Moiré. The Moiré optical technique showed great quality scanning of surfaces, as well as presented high speed and accuracy in comparison to the traditional methods.